Preoperative CA125 Significantly Improves Risk Stratification in High-Grade Endometrial Cancer - Lombaers Marike S.; Cornel Karlijn M. C.; Visser Nicole C. M.; Bulten Johan; Kuesters-Vandevelde Heidi V. N.; Amant Frederic; Boll Dorry; Bronsert Peter; Colas Eva; Geomini Peggy M. A. J.; Gil-Moreno Antonio; van Hamont Dennis; et al. (MDPI, 2025)
Simple Summary Patients with high-grade uterine cancer (UC) have a risk of around 20% of the cancer spreading to the lymph nodes, while this is only around 10% in patients with low-grade uterine cancer. CA125 is a marker that can be detected in blood and is associated with increased tumor spread. Studies on CA125 and its association with tumor spread within low-grade UC exist but are limited for high-grade UC. The primary aim of this retrospective study was to assess whether elevated CA125 is predictive for UC spread and survival. Secondarily, we studied the additional value of preoperative imaging by CT scan in relation to CA125 specifically in high-grade UC. We observed that elevated CA125 was related to advanced stage and LNM in high-grade UC and a worse prognosis. If CA125 was normal, the additional value of CT to predict lymph node spread was limited.Abstract Patients with high-grade endometrial carcinoma (EC) have an increased risk of tumor spread and lymph node metastasis (LNM). Preoperative imaging and CA125 can be used in work-up. As data on cancer antigen 125 (CA125) in high-grade EC are limited, we aimed to study primarily the predictive value of CA125, and secondarily the contributive value of computed tomography (CT) for advanced stage and LNM. Patients with high-grade EC (n = 333) and available preoperative CA125 were included retrospectively. The association of CA125 and CT findings with LNM was analyzed by logistic regression. Elevated CA125 ((>35 U/mL), (35.2% (68/193)) was significantly associated with stage III-IV disease (60.3% (41/68)) compared with normal CA125 (20.8% (26/125), [p < 0.001]), and with reduced disease-specific-(DSS) (p < 0.001) and overall survival (OS) (p < 0.001). The overall accuracy of predicting LNM by CT resulted in an area under the curve (AUC) of 0.623 (p < 0.001) independent of CA125. Stratification by CA125 resulted in an AUC of 0.484 (normal), and 0.660 (elevated). In multivariate analysis elevated CA125, non-endometrioid histology, pathological deep myometrial invasion >= 50%, and cervical involvement were significant predictors of LNM, whereas suspected LNM on CT was not. This shows that elevated CA125 is a relevant independent predictor of advanced stage and outcome specifically in high-grade EC.